A survey on the basic understanding of simple harmonic motion among physics university students - Mohd Yusoff, Mohd Zaki (GADING Journal for the Social Sciences, 2024)
A survey was conducted on 24 students aged 20–23, representing 56.7% female and 33.3% male. Two groups were formed: industrial physics and education degree students. According to the survey, 95.8% of students were able to answer questions about oscillatory motion, phase constant, simple harmonic oscillator energy, and potential energy. However, some students still struggled with the concept of simple harmonic motion (SHM). The survey revealed that 41.7% of students found SHM: Introduction easy to understand, followed by the simple pendulum, mass-spring system, energy of the SHM, and phase angle. The most difficult topics were phase angle, SHM energy, and simple pendulum. There are many equations students need to remember when working on the phase angle and SHM energy. Students had problems in understanding sinusoidal graphs, misinterpreting period motion graphs, and solving restoring force calculations.